1991
DOI: 10.2307/1591604
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electrocardiographic Analysis for Investigation of Ascites Syndrome in Broiler Chickens

Abstract: This study was conducted (at high altitude [1969 meters]) to determine whether chicks predisposed to cardiac failure and ascites could be identified and followed during growout with non-invasive electrocardiographic (ECG) techniques. ECG recordings were made on 40 chicks at 1 week of age. All recordings were analyzed by quantifying the amplitude in millivolts of the R-, S-, and T-waves in each of the recordings. During the study, ascites-related mortality was 40%, with the majority of the deaths occurring betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
4

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 15 publications
1
8
0
4
Order By: Relevance
“…When the RV wall hypertrophies the right atrioventricular valve also hypertrophies, leading to valvular insufficiency and RVF Qulian, 1987). Genetic or congenital differences in the RV wall or valve may make some broilers even more susceptible to PH-induced RVF as suggested by structural and electrocardiographic studies (Asson-Batres et al, 1989;Odom et al, 1989Odom et al, , 1991Odom et al, , 1992cMartinez et al, 1992).…”
Section: Pathogenesis Of Pulmonary Hypertensionmentioning
confidence: 99%
“…When the RV wall hypertrophies the right atrioventricular valve also hypertrophies, leading to valvular insufficiency and RVF Qulian, 1987). Genetic or congenital differences in the RV wall or valve may make some broilers even more susceptible to PH-induced RVF as suggested by structural and electrocardiographic studies (Asson-Batres et al, 1989;Odom et al, 1989Odom et al, , 1991Odom et al, , 1992cMartinez et al, 1992).…”
Section: Pathogenesis Of Pulmonary Hypertensionmentioning
confidence: 99%
“…Standard electrocardiogram (ECG) limb lead configurations, typical ECG wave segments, and standard degree-vector alignments for the frontal plane mean electrical axis (MEA; degrees) and mean resultant vector amplitude (MRV, millivolts) have been described for mammals and birds (Sturkie, 1986;Guyton, 1991;Odom et al, 1991;Conover, 1992). Owen et al (1990) first reported increased ECG lead II RS wave amplitudes when pulmonary hypertension and cardiac hypertrophy were triggered by exposing broilers to hypobaric hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…Electrocardiography (ECG) has been shown to be an effective tool for determining if a bird is developing ascites. Reports have indicated that speci®c ECG changes, such as negative Lead II S-wave amplitudes are predictive of elevated right ventricle to total ventricle ratios (Owen et al, 1990(Owen et al, , 1995aOdom et al, 1991Odom et al, , 1992cKirby, 1995, 1996;Wideman et al, 1997Wideman et al, , 1998b. Pulmonary arterial pressure can be measured directly through the use of a venous catheter (Guthrie et al, 1987;Owen et al, 1995c;.…”
Section: Genetic Selection Methodsmentioning
confidence: 99%